Peran BEM UNBARA Sebagai Aktor Civil Society dalam Mengawal Transparansi dan Akuntabilitas Pemerintahan Daerah - Varel Arga Pratama; Ayu Tri Wulandari; Alya Agustia; Jessieeca Okta Ramadhona (Departemen Budidaya Tanaman Perkebunan, Fakultas Pertanian, Universitas Andalas, 2026)
The principles of Transparency and Accountability are the main pillars of Good Governance which are vital for the success of Regional Autonomy, but their implementation is often hampered by deviant practices. The UNBARA Student Executive Board (BEM) positions itself as a Civil Society actor supported by idealism, moral values and a legal basis (UU KIP), tasked with carrying out social control over regional government. This research aims to analyze the implementation of BEM UNBARA's role in guarding Transparency and Accountability, especially in responding to crucial issues such as the follow-up to the KPK Hand Capture Operation (OTT) in the area, as well as identifying challenges and their sustainability strategies. This qualitative research using a case study approach was carried out in OKU Regency with a focus on BEM UNBARA. Primary data was collected through in-depth interviews with BEM administrators, and secondary data from study documents, local media, and regional policy documents (APBD, RPJMD). Data analysis uses an interactive model (reduction, presentation and conclusion) which is supported by data triangulation. BEM UNBARA implements its role in layers: (1) Real Action and Social Control: The most significant is the post-OTT KPK demonstration, which aims to urge transparency of the legal process and demand accountability of regional officials. (2) Layered Advocacy Strategy: Expressing aspirations is carried out starting from official hearings and written recommendations, to using demonstrations as the final step to pressure the government's response. (3) Challenges and Sustainability: The main challenges are limited access to official data and political stigma, which BEM overcomes through strengthening collaboration with CSOs/local media and internal institutionalization (cadre formation and regulation) to ensure the sustainability of supervision in the future. The impact of BEM's involvement is increasing public awareness and opening up space for dialogue with the government